Copperheads : the rise and fall of Lincoln's opponents in the North - Weber, Jennifer L., 1962- (OUP E-Books., 2006)
If Civil War battlefields saw vast carnage, the Northern home-front was itself far from tranquil. Fierce political debates set communities on edge, spurred secret plots against the Union, and triggered widespread violence, such as the New York City draft riots. And at the heart of all this turmoil stood Northern anti-war Democrats, nicknamed "Copperheads." Now, Jennifer L. Weber offers the first full-length portrait of this powerful faction to appear in almost half a century. Weber reveals how the Copperheads came perilously close to defeating Lincoln and ending the war in the South.